1997
DOI: 10.1111/j.1532-5415.1997.tb03202.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use Over Time in a Rural Older Adult Population: The MoVIES Project

Abstract: Overall, our data on antidepressant use in this rural older population mirror national trends away from tricyclics and towards SSRIs. Our findings also suggest underutilization of mental health services and antidepressant drugs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
4
15
1
Order By: Relevance
“…As has been previously observed, we found women to have higher CES-D scores than men and also to be more often treated with antidepressants (Brown et al, 1995;Ganguli et al, 1997;Aparasu et al, 2003;Percudani et al, 2005). Surprisingly, in subjects with current MDD, women had lower CES-D scores and were less often treated than men.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As has been previously observed, we found women to have higher CES-D scores than men and also to be more often treated with antidepressants (Brown et al, 1995;Ganguli et al, 1997;Aparasu et al, 2003;Percudani et al, 2005). Surprisingly, in subjects with current MDD, women had lower CES-D scores and were less often treated than men.…”
Section: Discussionsupporting
confidence: 72%
“…Epidemiological studies in elderly populations have shown that use of antidepressants is associated with sociodemographic factors (Brown et al, 1995;Ganguli et al, 1997;Blazer et al, 2000), selfperceived health (Blazer et al, 2005) and increases with frequency of visits to general practitioners and overall drug consumption (Sleath et al, 2005). Few studies have, however, examined these factors in relation to the severity of depression symptoms.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, according to Gao et al (2009) depressive signs are greater among elderly people living in rural areas, because the access to mental health service is more difficult. In contrast, Carpiniello, Carta, and Rudas (1989) and Ganguli, Mulsant Richards, Stoehr, and Mendelsohn (1997) found the opposite pattern of results. This discrepancy may be significant inasmuch as it suggests residential environment is an important factor in depression in the elderly.…”
Section: Introductioncontrasting
confidence: 56%
“…Among its consequences are reduced life satisfaction and quality of life, social deprivation, loneliness, increased use of health and home care services, cognitive decline, impairments in activities of daily living, chronicity, suicide, and an increased non-suicide mortality (Palsson and Skoog, 1997). Despite these outcomes, several studies have found a low rate of treatment for geriatric depression (Livingston et al, 1990;Copeland et al, 1987;Bowling, 1990;Keller et al, 1995;Girling et al, 1995;Forsell et al, 1995;Ganguli et al, 1997). There have been a modest number of clinical trials of antidepressants in geriatric depression, primarily examining tricyclic antidepressants and selective serotonin reuptake inhibitors (SSRIs).…”
Section: Introductionmentioning
confidence: 95%